Can Underlying Co-Morbidities Affect Cerebral Oximetry in Cardiac Surgery Patients? - Kianoush Saberi; Shahnaz Sharifi; Amirhossein Orandi (Acta Medica Iranica)
Today, there is a growing number of monitoring Equipment accessible. These equipments ranging invasive to non-invasive. Choosing suitable monitoring methods depends on their benefits, drawbacks, and expenses. Overall, non-invasive brain monitoring is growing in importance because of its precision in performance and increased stability in output. Like the assessment of regional brain oxygen levels and the assessment of anesthesia depth using the BIS device, whose specific role in guidelines remains undefined. Many patients who undergo heart surgeries including valvular, dissection and CABG have various comorbidities. To add details, according to literatures about CVA 28% of patients had (Cerebrovascular Accident), 74% IHD (Ischemic Heart Disease), 82% HTN (Hypertension), 52% DM (Diabetes Mellitus), 61% Smoking History, 36% CKD (Chronic Kidney Disease) and 42% CHF (Congestive Heart Failure). Current study delves into the correlation of short-term complications after cardiac operations with cerebral oximetry alterations and the space under the curve (duration of rSo2 drop) to take the best advantages of cerebral oximetry for heart surgery in the future. This prospective observational study was conducted among 101 patients undergoing cardiac surgery at Imam Khomeini Hospital in Tehran between 2019 and 2020. Following admission to the operating room, standard monitoring of vital signs, including non-invasive blood pressure (NIBP), electrocardiogram (ECG), central venous pressure (CVP), oxygen saturation (SpO2), and end-tidal carbon dioxide (ETCO2), was established. Prior to anesthesia induction, cerebral oxygen saturation (rSO2) was continuously monitored using the INVOS 5100c cerebral oximeter. Patients were followed for 7 days postoperatively, with documentation of intubation duration, intensive care unit (ICU) stay, and complications such as renal failure, cerebrovascular accident (CVA), and mortality. Data analysis was performed using SPSS 25.0 statistical software, with a P of less than 0.05 considered statistically significant. This study investigated rSO2 levels, as measured by a cerebral oximeter, in patients aged 19 to 79 undergoing cardiac surgery. Data were collected from both the right and left sides of the forehead during the operative period. Overall, these findings highlight the importance of rSO2 monitoring during cardiac surgery, particularly in patients with underlying cardiovascular conditions. Further research is needed to elucidate the specific mechanisms underlying these observations and to explore potential strategies for optimizing cerebral oxygenation in this vulnerable patient population.